Reliability Analysis of OCR Relay with ETAP 19.0.1 Simulation to Anticipate Disturbances in Bemo Feeders at the Cawang Lama Substation - Aditya, Lukman; Eriawan, Eriawan; Albahar, Abdul Kodir (Departemen Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2025)
The protection system is an important part of the electricity distribution system. Setting the protection relai is a significant procedure that must be ensured properly, so that the relai can work optimally when it experiences interference. If the disturbance is not cut off by the OCR Relay on the feeder, it could result in the incoming tripping, effecting in losses to PLN. Analysis is carried out to determine the reliability of the over current relai (OCR) so that the electric power system remains stable. The relay used by the Cawang Lama Substation is Standard Inverse, where the greater the fault current, the faster the relay working time and vice versa. In this research, simulations were carried out using ETAP 19.0.1, testing and calculations. ETAP simulation shows that protection coordination is appropriate. The relai on the feeder trips first with a time setting of 0.15 s for over current (OC) and 0.2 s for moment over current (MOC), then at incoming 0.24 s for OC and 0.5 s for MOC. The results obtained from the analysis of relay working time on the Bemo feeder up to the power breaker trip (PMT), namely 0.256 s using calculations, 0.275 s using Current Injector, and 0.260 s using ETAP simulation. From a comparison of the working time of the relay, it’s obtained between 0.04 s - 0.019 s, and this value is still considered proper